Association between desloratadine and prednisolone in the treatment of children with acute symptoms of allergic rhinitis: a double-blind, randomized and controlled clinical trial - Wandalsen,Gustavo F. (2017)
Abstract Introduction: A combination of antihistamines and oral corticosteroids is often used to treat acute symptoms of allergic rhinitis. Objective: To evaluate safety and efficacy of desloratadine plus prednisolone in the treatment of acute symptoms of children (2-12 years) with allergic rhinitis, and to compare it to dexchlorpheniramine plus betamethasone. Methods: Children with moderate/severe persistent allergic rhinitis and symptomatic (nasal symptoms score [0-12] ≥ 6) were allocated in a double-blind, randomized fashion to receive dexchlorpheniramine plus betamethasone (n = 105; three daily doses) or desloratadine plus prednisolone (n = 105; single dose followed by two of placebo) for 7 days. At the beginning and end of the evaluation, the following were obtained: nasal symptoms score, extra nasal symptoms score, peak nasal inspiratory flow, blood biochemistry, and electrocardiogram. Ninety-six children of the dexchlorpheniramine plus betamethasone group and 98 of the desloratadine plus prednisolone group completed the protocol. Results: The two groups were similar regarding initial and final nasal symptoms scores, extra nasal symptoms scores and peak nasal inspiratory flow. A drop of 76.4% and 79.1% for nasal symptoms score, 86.0% and 79.2% for extra nasal symptoms score, as well as an increase of 25.2% and 24.3% for peak nasal inspiratory flow occurred for those treated with desloratadine plus prednisolone and dexchlorpheniramine plus betamethasone, respectively. There were no significant changes in blood chemistry. Sinus tachycardia was the most frequent electrocardiogram change, but with no clinical significance. Drowsiness was reported significantly more often among those of dexchlorpheniramine plus betamethasone group (17.14% × 8.57%, respectively). Conclusion: The desloratadine plus prednisolone combination was able to effectively control acute symptoms of rhinitis in children, improving symptoms and nasal function. Compared to the dexchlorpheniramine plus betamethasone combination, it showed similar clinical action, but with a lower incidence of adverse events and higher dosing convenience.